Solitaire and Brahms - Dreher, Sarah (New Victoria Publishers, 1997)
A lesbian romance set in the 1960s when such a relationship could lead to loss of job or apartment, even incarceration in a mental institution. The heroine is Shelby Camden, 25, a journalist engaged to a doctor, who discovers she is lesbian.